Development of choco-pinipig cereal drink - Umali, Katherine Tabtab
ABSTRACT Chocolate drink combined with pinipig particles was developed to encourage the use of locally available materials in producing a cheap yet highly nutritious cereal drink. The study was conducted in four phases. As a preliminary study, the most acceptable cocoa powder was determined by sensory evaluation. Brand A cocoa powder was selected based on chocolate flavor and economics. In Phase I, the most acceptable cocoa powder to powdered milk ratio was determined also by means of subjective analysis. The 45%:20% cocoa to milk ratio was selected since it had the most acceptable chocolate flavor. Moreover, the toasting time for pinipig was also determined with the toasted pinipig flavor and the mouthfeel as basis. Results of the sensor evaluation showed that the pinipig with 6-minute toasting time was preferred by the panelists. Phase II involved the characterization of the product through proximate and physico-chemical tests. The product with pinipig generally yielded higher nutritional values than the plain choco-pinipig powder. The pH, total soluble solids, and the water activity of the choco-pinipig powder were taken as well. Phase III involved the shelf life study of the product through microbiological analyses. The product was found to be shelf stable but not microbiologically safe. In Phase IV, consumer acceptability of the product was determined. Generally, the product was well accepted by the consumers. Most of the panelists rated the choco-pinipig cereal drink to have a very good quality, one that was liked very much and one which they would frequently consume.